2020
DOI: 10.2147/cia.s251025
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Randomized Controlled Trial of FNB versus FICB for Patients with Femoral Neck Fractures Before Spinal Anesthesia</p>

et al.

Abstract: Background and Objectives: Patients with femoral neck fractures often suffer severe pain. This randomized controlled clinical study compared the effect of femoral nerve block (FNB) and fascia iliaca compartment block (FICB) in this population. Patients and Methods: Forty-six patients were randomly assigned to one of the two groups: FNB group (femoral nerve block, n=23) or FICB group (fascia iliaca compartment block, n=23). Before positioning for spinal anesthesia, patients received FNB with 15 mL of 0.5% ropiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Our results were similar to other studies that have reported high satisfaction with PENG block[ 4 5 29 ] as well as FICB. [ 30 ] No patient reported any LA toxicity or block-related complication.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to other studies that have reported high satisfaction with PENG block[ 4 5 29 ] as well as FICB. [ 30 ] No patient reported any LA toxicity or block-related complication.…”
Section: Discussionmentioning
confidence: 99%
“…An electronic search yielded 861 potential records, including 229 duplicate articles. Six hundred and eighty-eight articles were identified as irrelevant by the titles and excerpts, leaving fourteen studies that eventually met the eligibility requirements [ 4 6 , 14 24 ]. The 14 RCTs enrolled 590 patients on the FNB group and 588 patients on the FICB group.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1 , the included studies were characterized by the following key characteristics: all available literature consists of relatively small sample sizes, ranging from 10 to 85 patients. Preoperatively nerve block was applied in 13 studies [ 4 6 , 14 18 , 20 24 ], and postoperative nerve block was used in 1 study [ 19 ]. 5 studies [ 6 , 16 , 20 , 22 , 23 ] employed the general anesthesia, 4 studies [ 4 , 5 , 14 , 19 ] used regional anesthesia, and 5 studies [ 15 , 17 , 18 , 21 , 24 ] did not mention the detailed method of anesthesia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations